DILEMATIK PEREMPUAN TENGANAN DALAM HAL KONSEP PERKAWINAN - Komang David Darmawan (Jurnal Ilmiah Cakrawarti, 2021)
Tenganan Village is on the eastern tip of the island of Bali. One of the original Balinese sub-tribes or commonly known as Bali Aga. Tenganan Village is rich in tradition and sustainable culture. The people also adhere to the traditional teachings passed down from their ancestors since long ago. One of the traditions of marriage in Tenganan Village is different from areas in Bali in general. In the tradition of marriage, the concept of endogamous marriage is used. Where this concept requires citizens to marry people from one region or one tribe. If this occurs in the marriage, it will be sanctioned in the form of a fine and maselong (banished) from Tenganan Village. This is what becomes mathematics for women in Tenganan in marriage.